Real-world experience on efficacy and safety of different adjuvant chemotherapy regimens in locoregionally advanced nasopharyngeal carcinoma - Jie Chen; Sai-Lan Liu; Qiu-Yan Chen; Lin-Quan Tang; Hai-Qiang Mai; Hui Cheng; Pan Wang; Yi-Fu Li; Yu-Chen Li; Hao-Xiang Long; Jie-Yi Lin; Chun Fung Tse; et al. (BMJ Oncology)
Objective This study aimed to evaluate the efficacy and toxicity of various adjuvant chemotherapy (AC) regimens for treating locoregionally advanced nasopharyngeal carcinoma.Methods and analysis In this retrospective study, the patients received either intravenous AC regimens (cisplatin–fluorouracil (PF) or cisplatin–gemcitabine (GP)) or oral regimens (capecitabine or tegafur, gimeracil and oteracil potassium capsule (S-1)) following concurrent chemoradiotherapy (CCRT). The primary endpoint was progression-free survival (PFS).Results A total of 229 patients were documented in the oral administration group (127 patients received capecitabine and 102 received S-1), whereas 241 patients were recorded in the intravenous group (164 patients received the PF regimen and 77 received the GP regimen). There was no significant difference in PFS between the intravenous and oral groups (n=154 each) after propensity score matching (3-year PFS rate: 76.3% vs 73.9%; HR, 0.803; 95% CI 0.523 to 1.233, p=0.316). However, based on the overall cohort, the GP regimen showed a superior 3-year PFS rate (89.1%) compared with PF (74.6%), capecitabine (76.0%) and S-1 (74.3%) regimen (p=0.005, 0.012 and 0.003, respectively), while multivariable analyses also demonstrated that the GP regimen (HRPFS, 0.38; 95% CI 0.18 to 0.81, p=0.012) was associated with better survival. Additionally, the intravenous group, which included PF and GP, exhibited a higher incidence of grade≥3 leucocytopenia (50.0% vs 22.7%), neutropenia (30.5% vs 18.2%), anaemia (16.2% vs 3.9%), hyponatraemia (3.2% vs 0) and hypokalaemia (12.3% vs 4.5%) than the oral group.Conclusion For patients treated with upfront CCRT, AC should be considered, and intravenous GP is preferred, although patients should be counselled about an increased risk of haematological toxicities. For patients treated with induction chemotherapy and CCRT, oral chemotherapy, either with capecitabine or S-1, was efficacious and tolerable.